PRIORITY DIRECTIONS OF THE STATE REGIONAL POLICY: DEVELOPMENT OF THE AGRICULTURAL SECTOR IN ORDER TO REDUCE POVERTY - Egamberdiev, Farmonqul; Muminov, Nozim Muminov; Kim, Tatyana; Elmonov, Bekmurod (International Journal of Psychosocial Rehabilitation, 2020)
The article defines the objectives of agricultural development in the system of territorial division of labor for the future, taking into account the emerging conditions of increasing water scarcity and environmental tension, and developed proposals for the reorientation of the territorial and intersectoral structure of the agro-industrial complex of the Republic on the basis of improving the specialization of agricultural production. At the same time, the main principles of the mechanism of economic regulation in the agro-industrial complex, capable of ensuring intersectoral changes taking into account the interests of the Republic, regions and producers of products, have been identified. The main purpose of the research is to define the task in the areas of poverty reduction, socio- economic development of the regions, transformation of enterprises with state participation, formation and implementation of investment policy, development of entrepreneurship in the country.